Parental Perceptions of Child's Play in the Post-Digital Era: Parents' Dilemma with Digital Formats Informing the Kindergarten Curriculum - Andreja Istenič; Violeta Rosanda; Marina Volk; Mateja Gačnik (MDPI AG, 2023)
Digital technology affordance has been recognized as a social and learning tool, and the requirements for digitalizing the kindergarten curriculum have been present for decades. Digitalization in a child's early years can present conflict with parents, as the societal and economic demands of digitalized society for a child's digital technology use are in dissonance with guidelines and recommendations of health organizations that caution against preschool children's technology use. Kindergarten curricular reform in Slovenia was conducted in the 1990s. In this period, the use of digital learning technology and digital play for the development of children learning predispositions and early literacy was already recognized. At the time of curriculum design, it integrated some elements of digital learning technology. Now, 30 years after the design of the new curriculum, we are facing the post-digital era. Learning technology in the early years is a matter of partnership with parents; accordingly, this descriptive survey study includes a non-randomized sample of 306 parents. We are considering how child's play is structured in the primary environment and how parents perceive digital technology in the current post-digital age of seamless, digitally saturated social practices. Parents are aware of the risks of technology and of its benefits for learning. The findings show correlations between a child's digital screen technology use and parents' attitudes and perceptions of digital play. Parents that offer digital screen technology to a child have less agreeable attitudes regarding its possible risks to a child.